(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The purpose of this study was to determine whether the effect of service convenience and service quality has an effect on customer loyalty, with customer satisfaction as a mediator. This research aims to provide an in-depth understanding of what factors can increase customer loyalty, both directly and indirectly. The data collection method uses a questionnaire distributed using Google Form. The method used is purposive sampling technique; the data is processed using multiple linear regression analysis with classical assumption tests and hypothesis testing using SPSS 25. The implementation of this research is to find out more about service convenience and service quality on customer loyalty and customer satisfaction as a mediator. This research will show a variety of different influences on customer loyalty. The results showed that service convenience and service quality generated from several literatures were shown to have a positive influence on customer loyalty, but the service convenience variable did not have a positive effect on customer satisfaction or service quality and also proved to affect customer satisfaction. The variable of customer convenience on customer loyalty is not mediated by customer satisfaction, while in service quality, the results show that the service quality variable on customer loyalty is not mediated by customer satisfaction.